If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 7) + -5 = 2(8 + 4x) + -2x Reorder the terms: 3(7 + 2x) + -5 = 2(8 + 4x) + -2x (7 * 3 + 2x * 3) + -5 = 2(8 + 4x) + -2x (21 + 6x) + -5 = 2(8 + 4x) + -2x Reorder the terms: 21 + -5 + 6x = 2(8 + 4x) + -2x Combine like terms: 21 + -5 = 16 16 + 6x = 2(8 + 4x) + -2x 16 + 6x = (8 * 2 + 4x * 2) + -2x 16 + 6x = (16 + 8x) + -2x Combine like terms: 8x + -2x = 6x 16 + 6x = 16 + 6x Add '-16' to each side of the equation. 16 + -16 + 6x = 16 + -16 + 6x Combine like terms: 16 + -16 = 0 0 + 6x = 16 + -16 + 6x 6x = 16 + -16 + 6x Combine like terms: 16 + -16 = 0 6x = 0 + 6x 6x = 6x Add '-6x' to each side of the equation. 6x + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 6x + -6x Combine like terms: 6x + -6x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5.9x+1.8(0)=6.7 | | 35x^2+22x+3=0 | | 6b+4b-2= | | 5.9(0)+1.8y=6.7 | | 3x^2=17x+28 | | 5.9x+1.8y=6.7 | | 3(x-2)=99 | | 2x+9.75-7x=5.1 | | 3m+4=5 | | 3xy=o | | 2y+3=0 | | t+3-3.2=3 | | 48=8.21*t | | 7u+5-4(-3u-1)=3(u-1) | | 48=.512n | | 11x^2+22x=0 | | t+6-3.2=3 | | 9*-8= | | n-13=15 | | -6m^2+5m+2=0 | | 11-3(4+a)=2a | | -5a-1=1-5a | | t^2-4=12 | | 2x^3+8x^2+10x+4=0 | | -5(x+8)=4-x | | -2v+8=8-8v+6v | | 6m^2-5m-2=0 | | 6x+2x=20x | | -12(-4)-(-3)= | | .75n-3=9 | | 14x^2+6x-8=0 | | 4(2x+4)=20 |